Blended Learning Models: Bridging Traditional and Digital Educational Practices - Haryanto, Andi (PT Mutiara Bustan Ilmu, 2024)
This study explores the effectiveness of constructivist and traditional approaches in teaching Arabic to beginners. The constructivist approach, grounded in active learning and real-world application, emphasizes learner engagement and collaborative learning. The traditional approach, however, focuses on structured grammar-based instruction, providing learners with a foundational understanding of language rules. Through a comparative analysis of two groups of beginners—one taught using a constructivist approach and the other using a traditional method—the research examines differences in engagement, motivation, and skill development (speaking, listening, reading, writing). Data was collected through classroom observations, interviews, and questionnaires to assess the participants' experiences and perceptions. Results indicate that learners in the constructivist group showed higher engagement and improved speaking and listening skills, while the traditional group excelled in reading and writing. Both approaches presented unique challenges, such as limited practical application in the traditional group and insufficient focus on grammatical accuracy in the constructivist group. The study concludes that a blended approach, combining the strengths of both methods, may provide the most comprehensive language learning experience for beginners.